Comparison of sequence of trunk and arm motions between short and long official distance groups in javelin throwing - Liu, H.; Leigh, S.; Yu, B. (Sports Biomechanics, 2014)
The purpose of this study was to determine the effects of sequences of the trunk and arm angular motions on the performance of javelin throwing. In this study, 32 male and 30 female elite javelin throwers participated and were separated into a short official distance group or a long official distance group in each gender. Three-dimensional coordinates of 21 body landmarks and 3 marks on the javelin in the best trial were collected for each subject. Joint center linear velocities and selected trunk and arm segment and joint angles and angular velocities were calculated. The times of the initiations of the selected segment and joint angular motions and maximum angular velocities were determined. The sequences of the initiations of the selected segment and joint angular motions and maximum angular velocities were compared between short and long official distance groups and between genders. The results demonstrated that short and long official distance groups employed similar sequences of the trunk and arm motions. Male and female javelin throwers employed different sequences of the trunk and arm motions. The sequences of the trunk and arm motions were different from those of the maximal joint center linear velocities.